2013
DOI: 10.1007/978-3-642-28409-0_5
|View full text |Cite
|
Sign up to set email alerts
|

Privacy-Aware Workflow Management

Abstract: Abstract. Information security policies play an important role in achieving information security. Confidentiality, Integrity, and Availability are classic information security goals attained by enforcing appropriate security policies. Workflow Management Systems (WfMSs) also benefit from inclusion of these policies to maintain the security of business-critical data. However, in typical WfMSs these policies are designed to enforce the organisation's security requirements but do not consider other external secur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
(14 reference statements)
0
9
0
1
Order By: Relevance
“…12. Alhaqbani et al, 2009) Suppose that the Service-Update agent decides to use incoming PII in another application, such as datamining software (e.g., for research purposes). Simply, the agent can do this only if the flow system shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12. Alhaqbani et al, 2009) Suppose that the Service-Update agent decides to use incoming PII in another application, such as datamining software (e.g., for research purposes). Simply, the agent can do this only if the flow system shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Proprietor role in access control: Alhaqbani et al (2009) used an example from the banking sector to illustrate a workflow model, shown in Fig. 14 (also Alhaqbani, 2010). The banking workflow model receives and processes customer requests and queries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regards, in [5] authors showed weaknesses of WfMSs to capture and enforce privacy policies such as conflict of interest, hiding personal data, or generalizing data, and provide extensions to the YAWL WfMS to cope with such issues. Similarly, Mülle et al [6] and Ciuciu et.…”
Section: Related Workmentioning
confidence: 99%
“…In [17] a subject notion is introduced that is added to the workflow design; the subject is the user. The workflow management system can then access the subject attribute, and from that retrieve the user's privacy policy and thus can enforce the privacy policies of the user in the workflow.…”
Section: Related Artmentioning
confidence: 99%